Mutations in ZIC3 and ACVR2B are a common cause of heterotaxy and associated cardiovascular anomalies - Ma, Lijiang; Selamet Tierney, Elif Seda; Lee, Teresa; Lanzano, Patricia; Chung, Wendy K. (Cardiology in the young, 2012)
Heterotaxy syndrome is caused by left-right asymmetry disturbances and is associated with abnormal lateralisation of the abdominal and thoracic organs. The heart is frequently involved and the severity of the abnormality usually determines the outcome. We performed a direct sequence analysis of the coding sequence of genes including Zinc Finger Protein of the Cerebellum 3, Left-Right Determination Factor 2, Activin A Receptor Type IIB, and Cryptic in 47 patients with laterality defects and congenital cardiac disease. Of the 47 patients, 31 (66%) had atrioventricular septal defects, 34 (72%) had abnormal systemic venous return, 25 (53%) had transposed or malposed great arteries, and 20 (43%) had pulmonary venous abnormalities. We identified two novel genetic changes in Zinc Finger Protein of the Cerebellum 3, and these variants were not present in 100 ethnically matched control samples. One previously reported missense mutation in Activin A Receptor Type IIB was identified in two unrelated subjects. The genetic changes identified in this study are all located in conserved regions and are predicted to affect protein function in left-right axis formation and cardiovascular development. Mutations in Zinc Finger Protein of the Cerebellum 3 and Activin A Receptor Type IIB were identified in 4 of the 47 patients with heterotaxy syndrome for a yield of approximately 8.5%. Our results expand the mutation spectrum of monogenic heterotaxy syndrome with associated cardiac anomalies and suggest that there are other causes of heterotaxy yet to be identified.